Comparison of Marketing Mix Determination on Purchasing Decisions of Pakde Jangkung Meatballs - Ria Rusty Yulita; Arief Daryanto; R Dikky Indrawawan (Universitas Tidar, 2021)
Bakso Pakde Jangkung is one of the restaurants that has the main product, namely meatballs. Bakso Pakde Jangkung is located in Bogor City, West Java, where Bakso Pakde Jangkung is not the only Bakso business in the form of a restaurant in the city.Currently there are problems related to the development of outlets and tenants as seen from the purchase decision. The factors tested using mix marketing and the analytical methods used are descriptive analysis and structural equational modeling. The test results show that there are differences in important factors at outlets and tenants related to purchasing decisions.